Contents and Contexts of Cyberbullying: An Epidemiologic Study using Electronic Detection and Social Network Analysis, Iowa, 2014-2015 - Ramirez, Marizen ([Verlag nicht ermittelbar], 2021)
Using a multi-methods research design, this study classified the contents of cyberbullying messages, measured their frequency and associations with offline bullying, and examined whether and how peer groups in social networks promote these behaviors. Beginning in January 2015, 164 adolescents from 2 Iowa middle schools, grades 6 through 8, were surveyed. Two surveys, one at the start of the spring semester and one at the end of spring 2015, gathered self-reported information on perpetration, victimization, and witnessing of online and offline bullying and the structure of peer networks. A total of 77 students furthermore participated in an electronic capture period from January through May 2015. Participant smartphones were equipped with an application that collected incoming and outgoing text messages and Facebook and Twitter activity, and also surveyed them weekly about their bullying experiences. Demographic information collected included age, grade, gender, ethnicity, parents' marital status, household composition, religiosity, and socioeconomic status.